Wealth effects of corporate real estate divestiture : impact from global financial crisis [electronic resource] - Ho, Wei Wui 1988- , author 638350 (2012)
Project Paper (Sarjana Muda Kejuruteraan (Pengurusan Harta)) - Universiti Teknologi Malaysia, 2012